Pengaruh Pelatihan, Tingkat Pendidikan, dan Sistem Pengendalian Internal terhadap Kualitas Laporan Keuangan di Instansi Pemerintah Kabupaten Maros - Iin Andriani; Ayu Puspitasari; Yudi Satria (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to determine the effect of training, education level, and internal control systems on the quality of financial reports in government agencies of Maros Regency. This study used a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 150 respondents who were financial management employees at 30 Regional Work Units (OPD) in Maros Regency, selected using purposive sampling. The data analysis techniques used included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²), assisted by the SPSS application. The results show that training, education level, and internal control systems each have a positive and significant partial effect on the quality of financial reports, with the internal control system being the most dominant contributing variable. Simultaneously, the three variables also have a significant effect on the quality of financial reports, with an R Square value of 0.484, indicating that the three variables explain 48.4% of the variation in financial report quality. This study recommends strengthening continuous training, aligning employee placement with educational background, and strengthening internal control systems to improve the accountability of regional financial management.